Regulating police detention : voices from behind closed doors (Policy Press shorts. Research., 2018)
Custody visitors are volunteers who make unannounced visits to police custody blocks to check on the welfare of detainees. However, there is a fundamental power imbalance between the police and these visitors. This timely book offers detailed proposals for radically reforming custody visiting to make it an effective regulator of police behaviour.